Facile synthesis and crystal structure of aGa22R8 cluster - Linti, Gerald W.; Rodig, Alexander (Chemical communications, 2000)
A new metalloid cluster Ga22R8 with a central gallium atom exhibiting an unusual coordination number of 13 and the gallatetrahedrane Ga4R4 are obtained by reaction of ‘GaI’ with the lithium tris(trimethylsilyl)germanide Li(thf)3R.
Gesehen am 16.03.2018
Im Titel ist "8", "22" tiefgestellt